Human Pulmonary Infection by the Zoonotic Metastrongylus salmi Nematode. The First Reported Case in the Americas - Calvopina, Manuel; Caballero, Henry; Morita, Tatsushi; Korenaga, Masataka (The American Society of Tropical Medicine and Hygiene, 2016)
Pulmonary metastrongylosis, a zoonotic disease found primarily in pigs, is caused by eight different species of the cosmopolitan nematode Metastrongylus genus. To date, only four human cases have been reported, all from Europe. Herein, a severe case of pulmonary infection caused by Metastrongylus salmi in an Ecuadorian man, with successful treatment with ivermectin, is described.